Equations and Formulas as Problem Solving Strategies Frequently Used by Students in Solving Math Problems - Salvador A. Loria Jr. (JPAIR Institutional Research Journal)
Problem solving is the core and primary objective of mathematics teaching. This study aimed to describe the problem solving abilities of sophomore engineering students of Nueva Ecija University of Science and Technology (NEUST) through the use of case study type, qualitative research method. Results showed that in terms of the ability to identify goals in a problem, the process of problem solving, and the skills of students in problem solving, the respondents showed a satisfactory performance. The most common method used by the respondents in problem solving was the use of equations or formulas, while the least preferred methods were the strategy of working backward and logical reasoning. The respondents displayed difficulty in answering problems in motion, geometry and set operation while the problems about sequence, rate, age, money/investment, combination, time were found easy to solve. Teachers and educators of mathematics are advised to develop instructional materials and activities that will equally address the three different context of problem solving, namely, goal of the problem, process in problem solving, and problem solving skills of students.